2022
DOI: 10.3389/fimmu.2022.968366
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic damage caused by long-term high cholesterol intake induces a dysfunctional restorative macrophage population in experimental NASH

Abstract: Excessive dietary cholesterol is preferentially stored in the liver, favoring the development of nonalcoholic steatohepatitis (NASH), characterized by progressive hepatic inflammation and fibrosis. Emerging evidence indicates a critical contribution of hepatic macrophages to NASH severity. However, the impact of cholesterol on these cells in the setting of NASH remains elusive. Here, we demonstrate that the dietary cholesterol content directly affects hepatic macrophage global gene expression. Our findings sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Conversely, the chronic tissue insult dysregulates the inflammatory response and favors fibrosis development ( 34 ). Fibrosis progression is marked by the activation of hepatic stellate cells (HSC) and hepatic macrophages, which secrete high levels of extracellular matrix compounds, unbalancing the restoration of the damaged tissue ( 35 , 36 ). At this stage, NK cells play a critical role in inducing early activated HSCs to apoptosis via cytotoxicity or IFN-γ secretion, thus delaying the progression of fibrogenesis ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the chronic tissue insult dysregulates the inflammatory response and favors fibrosis development ( 34 ). Fibrosis progression is marked by the activation of hepatic stellate cells (HSC) and hepatic macrophages, which secrete high levels of extracellular matrix compounds, unbalancing the restoration of the damaged tissue ( 35 , 36 ). At this stage, NK cells play a critical role in inducing early activated HSCs to apoptosis via cytotoxicity or IFN-γ secretion, thus delaying the progression of fibrogenesis ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, strategies devoted to improving NKT cell-mediated immune responses might represent a possible therapeutic approach to control HCC development in NASH. Cholesterol accumulation also fosters the differentiation of dysfunctional restorative macrophages which persists even after cholesterol restriction [ 121 ]. Metabolic factors in combination with chronic antigen stimulation also impact on T-cells by favoring the hepatic accumulation of CD4 + and CD8 + T-cells expressing the thymocyte selection associated high mobility group box protein (TOX), a nuclear factor leading to the acquisition of an exhausted phenotype.…”
Section: Immunomodulating Mechanisms Underlying Nash-related Hccmentioning
confidence: 99%
“…In addition, it was discovered that systemic cholesterol levels influence cellular cholesterol homeostasis in lipid-laden KCs ( 100 ). During hypercholesterolemia, macrophage cholesterol efflux is impaired, this drives their polarization towards a proinflammatory phenotype ( 115 , 116 ). The association is strong between dietary cholesterol intake and hepatic cholesterol in the development of NASH in both human and animal models.…”
Section: Macrophage Lipid Processing In Nafldmentioning
confidence: 99%
“…This is supported by large scale epidemiological studies, where dietary cholesterol consumption was independently associated with the development of NASH and cirrhosis ( 118 , 119 ). It has also been shown that the beginning of hypercholesterolemia might affect membrane fluidity, which, in turn, can cause changes in phagocytic capacity, a process known to be disrupted in murine models of NASH ( 115 , 119 121 ). It is speculated that the KCs scavenged free cholesterol (including crystals), cholesterol esters, and triglycerides from the remaining big lipid droplets of dying hepatocytes.…”
Section: Macrophage Lipid Processing In Nafldmentioning
confidence: 99%